Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Simply the expression below

(10-3i)(2-5i)


Sagot :

Answer:

7i and 3i

hope this helps <33

Answer:

Step-by-step explanation:

Use foil method

(10 - 3i) (2 -5i) = 10*2 + 10*(-5i)  +  (-3i)*2 + (-3i)*(-5i)

   = 20 - 50i -6i + 15i²

   = 20 - 50i - 6i + 15*(-1)             {i² = -1}

   = 20  - 50i - 6i - 15

   = 20 - 15 - 50i - 6i

   = 5 - 56i